Alterations in time intervals of ductus venosus and atrioventricular flow velocity waveforms in growth‐restricted fetuses. (August 2015) - Wada, N.; Tachibana, D.; Kurihara, Y.; Nakagawa, K.; Nakano, A.; Terada, H.; Tanaka, K.; Fukui, M.; Koyama, M.; Hecher, K.
Abstract Objective To investigate time intervals of the ductus venosus (DV) flow velocity waveform (FVW) and those of the cardiac cycle that correspond with each DV‐FVW component in fetuses with intrauterine growth restriction (IUGR) due to placental insufficiency. Methods Women with a pregnancy complicated by IUGR were recruited into the study, as was a normal control group. Time intervals for systolic (S) and diastolic (D) components were measured in DV‐FVW as follows: SDV, from the nadir of the a‐wave during atrial contraction to the nadir between the S‐wave and D‐wave; DDV, from the nadir between S‐wave and D‐wave to the nadir of the a‐wave. Regarding cardiac cycles, the following variables were measured from ventricular inflow through the tricuspid valve (TV) and mitral valve (MV): STV and SMV, from the second peak of ventricular inflow caused by atrial contraction (A‐wave) to the opening of the atrioventricular valve; DTV and DMV, from the opening of the atrioventricular valve to the peak of the A‐wave. In the IUGR group, only the last examination performed within 1 week of delivery was used for analysis. All variables were analyzed statistically using Z‐scores. Results Data were obtained from 249 normal fetuses and 26 fetuses with IUGR. Compared to normal fetuses, SDV showed a significant decrease (P < 0.001), while DDV showed a significant increase (P < 0.001) in the IUGR group. Regarding cardiac cycles, STV and SMV showed significant decreases (P = 0.014 and P < 0.001, respectively) and DTV and DMV showed significant increases (P = 0.008 and P = 0.002, respectively) in fetuses with IUGR. Conclusion Time‐interval alterations of DV‐FVW in growth‐restricted fetuses reflect the hemodynamic events caused by placental insufficiency. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.